Incidence of mesorectal node metastasis in locally advanced cervical cancer: its therapeutic implications. Issue 1 (January 2019) - Cordero-Gallardo, Francisco; Lee Burnett, O; McNamara, Michelle M; Weber, Therese M; Zarzour, Jessica; Bae, Sejong; Jang, Samuel; Barrett, Olivia Claire; McDonald, Andrew; Kim, Robert Y
Abstract : Objective: To evaluate the incidence and risk factors for mesorectal node metastasis (MRNM) in locally advanced cervical cancer. Methods/Materials: We performed an observational retrospective cohort study of 122 patients with cervical cancer who received definitive chemo-radiation treatment between December 2013 and June 2017 to evaluate the incidence of MRNM. Three diagnostic radiologists assessed all available pre-treatment images. In this study, the pelvic node metastasis was defined as ≥ 1.0 cm and MRNM as ≥ 0.5 cm for CT and MRI scans and as a maximum standardized uptake value of > 2.5 for PET/CT. The relationship of MRNM with FIGO stage, pelvic node metastasis, and mesorectal fascia involvement was evaluated. Results: The incidence of MRNM in all 122 patients was 8 (6.6%). However, in advanced stage (III– IV) patients, MRNM occurred in 4 of 39 (10.3%) compared with 4 of 83 (4.8%) in early stage (IB1–IIB) patients (p = 0.27). In patients with a positive pelvic node, MRNM occurred in 7 of 55 (12.7%) and 1 of 67 (1.5%) in those with negative pelvic node (p = 0.02). In addition, the incidence of MRNM was 3 of 9 (33.3%) in the presence of mesorectal fascia involvement and 5 of 113 (4.4%) among those without mesorectal fascia involvement (p = 0.013). Conclusion: This study indicates that pelvic node metastasis and mesorectal fascia involvement are high-risk factors for MRNM. Therefore, vigilance of reviewing images in the mesorectum for MRNM is necessary for high-risk patients.